Nível motivacional para a prática esportiva em escolares: Fatores de influência - Oliveira, Vinicius Machado de (2020)
This study aimed to analyze the sport motivation and its influence factors in Brazilian elementary and high school students. A total of 846 schoolchildren (439 boys, 407 girls) aged 10 to 19 participated in the study. The Sport Motivation Scale (SMS) was used to survey the sport motivation. The instrument aims at verifying the levels of intrinsic and extrinsic motivation for sport, as well as cases of demotivation. For statistical purposes, the data were submitted to the Mann Whitney test. After analysis, it was found that male students are more motivated than female students. In this same direction, it was also found that younger students -and in initial stages of schooling- have higher motivational scores than older students. Another influence factor verified in the analysis was the practice environment, in which training contexts manage to provide more intense motivational climates than the school. Finally, collective modalities are better associated with extrinsic motivations while individual practices indicate greater proximity to intrinsic motivations.